Taxonomic notes on the Evaniidae (Hymenoptera) described by J. Brèthes - Martinez, Juan Jose (2009)
A The French-Argentine entomologist Jean Brèthes described many species, mainly in the insect orders Diptera and Hymenoptera, during the first three decades of the 20th century. Most of the specimens studied by Brèthes are housed at the Entomology Division of the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia” in disparate states of preservation and curation. The statuses of many of Brèthes’s specimens labeled as types need to be ascertained (e.g., Quicke & Genise 1990), since Brèthes mislabeled many specimens and classified others under nomina nuda (personal observation). This, together with important changes in the classification of most insect orders since the times of Brèthes, make it necessary to reexamine the material that he studied and to recognize overlooked type specimens which have remained unnoticed within the general collection of the museum, as recently mentioned for Colpotrochia flava (Brèthes) (Martinez 2008).